Hepatic steatosis among chronic hepatitis C infected patients selected for treatment - a retrospective analysis - Jaafar, Khairul Azhar; Hasmoni, Mohamed Hadzri; Abdul Rashid, Mohd Amran; Md Ralib @ Md Raghib, Ahmad Razali; H, Nora; Satwi, Sapari (Springer, 2008)

(untitled)
Hepatic steatosis is a common feature of chronic hepatitis C (CHC). It is caused directly by the virus (genotype 3)or host metabolic factors. We analyzed liver biopsy results among all patients selected for the treatment. Methods: We retrospectively looked into CHC patients selected for treatment from 2005 - 2007,Kuantan Hospital, Malaysia. Fifteen patients were identified between the ages of 19 - 58 years. Blood results for HCV RNA viral load, genotyping, lipid profile, liver biopsy (Ishak et al score) and body mass index (BMI) were documented pretreatment. Results: Seven patients were genotype 1, 6 patients were genotype 3 and 1 patient each for genotype 2 and 6 respectively. Majority of patients had mild hepatic steatosis, 60% (n=9/15) pretreatment and highest were among genotype 1, 33.3% (n=5/15), followed by genotype 3, 20% (n=3/15) and genotype 2, 6% (n=1/15). Among them, 8 out of 15 (53.3%) patients had normal trigliseride (TG) level, 5 out of 15 (33.3%) patients had BMI <25 and 6 out of 15 (40%) patients had high viral load (HVL, >400,000 iu/ml). Conclusions: We observed that the majority of patients with CHC had mild hepatic steatosis, 60% (n=9/15) with normal TG, 53.3% (n=8/15) and amongst genotype 1, 33.3% (n=5/15). Higher viral load might have an influence in the development and progression of steatosis in CHC.